Redox dyshomeostasis modulation of the tumor intracellular environment through a metabolic intervention strategy for enhanced photodynamic therapy - Yang, Zuo (2023)
Rationale: Photodynamic therapy (PDT) is a clinically approved anticancer treatment with a promising therapeutic prospect, however, usually suffers from the unfavorable intracellular environment including cellular hypoxia and excessive glutathione (GSH). Comprehensive and long-term modulation of tumor intracellular environment is crucial for optimizing therapeutic outcomes. However, current strategies do not enable such requirements, mainly limited by flexible networks of intracellular metabolic avenues. Methods: A metabolic pre-intervention (MPI) strategy that targets critical pathways of cellular metabolism, ensuring long-term modulation of the intracellular environment. A versatile lipid-coating photosensitive metal-organic framework (MOF) nano-vehicle encapsulating aerobic respiration inhibitor metformin (Met) and GSH biosynthesis inhibitor buthionine sulfoximine (BSO) (termed PBMLR) was developed for comprehensive sustainable hypoxia alleviation and GSH downregulating. Results: Since MPI could effectively circumvent the compensatory accessory pathway, PBMLR, therefore functioned as an efficient singlet oxygen (1O2) radical generator during the subsequent laser irradiation process and enhanced PDT anti-tumor efficiency. We emphasized the concordance of long-term hypoxia alleviation, persistent GSH depletion, and tumor enrichment of photosensitizers, which is very meaningful for a broad therapeutic time window and the successful enhancement of PDT. Conclusion: Our findings indicate that maintaining the sensitivity of tumor cells via MPI could enhance anti-tumor PDT, and may be applied to other dynamic therapies such as radiodynamic therapy and sonodynamic therapy.